Tailored Unilobar and Multilobar Resections for Orbitofrontal-Plus Epilepsy. Issue 4 (3rd July 2014) - Serletis, Demitre; Bulacio, Juan; Alexopoulos, Andreas; Najm, Imad; Bingaman, William; González-Martínez, Jorge
Abstract: BACKGROUND: Surgery for frontal lobe epilepsy often has poor results, likely because of incomplete resection of the epileptogenic zone. OBJECTIVE: To present our experience with a series of patients manifesting 2 different anatomo-electro-clinical patterns of refractory orbitofrontal epilepsy, necessitating different surgical approaches for resection in each group. METHODS: Eleven patients with refractory epilepsy involving the orbitofrontal region were consecutively identified over 3 years in whom stereoelectroencephalography identified the epileptogenic zone. All patients underwent preoperative evaluation, stereoelectroencephalography, and postoperative magnetic resonance imaging. Demographic features, seizure semiology, imaging characteristics, location of the epileptogenic zone, surgical resection site, and pathological diagnosis were analyzed. Surgical outcome was correlated with type of resection. RESULTS: Five patients exhibited orbitofrontal plus frontal epilepsy with the epileptogenic zone consistently residing in the frontal lobe; after surgery, 4 patients were free of disabling seizures (Engel I) and 1 patient improved (Engel II). The remaining 6 patients had multilobar epilepsy with the epileptogenic zone located in the orbitofrontal cortex associated with the temporal polar region (orbitofrontal plus temporal polar epilepsy). After surgery, all 6 patients were free of disabling seizures (Engel I). Pathology confirmed focal cortical dysplasia in all patients. We report no complications or mortalities in this series. CONCLUSION: Our findings highlight the importance of differentiating between orbitofrontal plus frontal and orbitofrontal plus temporal polar epilepsy in patients afflicted with seizures involving the orbitofrontal cortex. For identified cases of orbitofrontal plus temporal polar epilepsy, a multilobar resection including the temporal pole may lead to improved postoperative outcomes with minimal morbidity or mortality.